Pengaruh karakteristik eksekutif, profitabilitas, dar dan capital intensity terhadap agresivitas pajak - Fahmi, Syarif; Yuliani, Rahma; Adriani, Ade (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Kalimantan province is an area rich in coal deposits. That reason has made many coal companies in Kalimantan. However, the number of companies differs from the tax revenue the Regional Office of the DJP of Central and South Kalimantan receives in the coal mining sector. This research was conducted to look at the effect of tax aggressiveness on coal mining sector taxpayers in the South and Central Kalimantan DGT Regional Office. The data used in this study is secondary data, where the data was obtained from the DGT Regional Offices in South Kalimantan and Central Kalimantan. The sample of this research is 71 Taxpayers in the Coal Mining Sector of the DGT Regional Office of South, and Central Kalimantan selected using predetermined criteria. Test results on research show that executive characteristics and profitability significantly influence tax aggressiveness. In contrast, DAR and capital intensity partially have no significant effect on the tax aggressiveness of coal mining sector taxpayers in the working areas of the DGT regional offices in South Kalimantan and Central Kalimantan.